Online Quantitative Literacy-Based Biology Learning towards Students' Self-Efficacy - Wafda Jamil, Muhamad; Nuraeni, Eni; Rahmat, Adi (KnE Social Sciences, 2024)
Quantitative literacy is an important skill for biology students. During COVID-19, students had to adapt to several changes, including shifting from offline to online classes. However, not all biology content can be taught easily, especially online. Therefore, students need self-efficacy abilities. Self-efficacy was important for students to be able to make a plan for their learning. This research aimed to describe students’ self-efficacy to continue their online biology learning during COVID-19, based on their quantitative literacy skills. This study used 20-item questionnaires with four choices of statements. The biology topic chosen was plant anatomy. This research measured the score of 82 first-year college students’ self-efficacy from three aspects - magnitude, strength, and generality. Data were analyzed using descriptive statistics to measure the mean, the highest, and the lowest students’ self-efficacy scores. The result showed that the average score of students’ self-efficacy was 2.72, which means students’ self-efficacy was in the moderate category. All three aspects were also in the moderate category, with the strength aspect score being the highest at 2.76 and the magnitude aspect score being the lowest at 2.66. Based on the number of participants’ level of self-efficacy, 3% of students were in the high category, 96% were in the moderate category, and 1% were in the low category. The result showed that most of the students in this research have a moderate level of self-efficacy in online biology learning, based on quantitative literacy. This means that most of the students still must develop their self-efficacy skills to learn online quantitative lessons in biology successfully. The results also suggested that it is essential to teach students how to manage their learning behavior through the development of self-efficacy to succeed in online quantitative lessons in biology learning in the future. Keywords: literacy, online class, self-efficacy